Downregulation of myogenic microRNAs in sub-chronic but not in sub-acute model of daunorubicin-induced cardiomyopathy - Doka, Gabriel; Malikova, Eva; Galkova, Kristina; La Rocca, Giampiero; Kruzliak, Peter; Adamek, Mariusz; Rodrigo, Luis; Krenek, Peter; Klimas, Jan (Molecular and cellular biochemistry, 2017)
Cardiac muscle-related microRNAs play important roles in cardiac development and disease by translational silencing of mRNAs, the dominant mechanism of microRNA action. To test whether they could be involved in daunorubicin-associated cardiomyopathy (DACM), we determined expression patterns of myomiRs in two distinct models of DACM. We used 10-12 weeks old male Wistar rats. In the sub-acute model, rats were administered with six doses of daunorubicin (DAU-A, 3 mg/kg, i.p., every 48 h). Rats were sacrificed two days after the last dose. In the sub-chronic model, anaesthetized rats were administered a single dose of daunorubicin (15 mg/kg, i.v., DAU-C). Age-matched controls (CON) received vehicle. Rats were sacrificed eight weeks later. Left ventricular (LV) functions (LV pressure, rate of pressure development, +dP/dt and decline, -dP/dt) were measured using left ventricular catheterization. Expressions of myomiRs (miR-208a, miR-499, miR-1 and miR-133a), markers of cardiac failure (atrial and brain natriuretic peptides genes; Nppa and Nppb) and myosin heavy chain genes (Myh6, Myh7, Myh7b) in cardiac tissue were determined by RT-PCR. Protein expression of gp91phox NADPH oxidase subunit was detected by immunoblotting. Both DAU groups exhibited a similar depression of LV function, and LV weight reduction, accompanied by an upregulation of natriuretic peptides, and a decrease of Myh6 to total Myh ratio (-18% in DAU-A and - 25% in DAU-C, as compared to controls; both P < 0.05). DAU-C, but not DAU-A rats had a 35% mortality rate and exhibited a significantly increased gp91phox expression (DAU-C: 197 ± 33 versus CON-C: 100 ± 11; P < 0.05). Interestingly, myomiRs levels were only reduced in DAU-C compared to CON-C (miR-208: -45%, miR-499: -30%, miR-1: -29%, miR- and miR133a: -25%; all P < 0.05) but were unaltered in DAU-A. The lack of myomiRs expression, particularly in sub-chronic model, suggests the loss of control of myomiRs network on late progression of DACM. We suppose that the poor inhibition of mRNA targets might contribute to chronic DACM.
Keywords: Muscle Proteins; down regulace; modely nemocí na zvířatech; Male; MicroRNAs; Rats, Wistar; Gene expression; Myosin heavy chain isoforms; Cardiomyopathies; svalové proteiny; mikro RNA; daunomycin; Cardiomyopathy; mužské pohlaví; potkani Wistar; kardiomyopatie; MicroRNA; krysa rodu Rattus; Animals; Down-Regulation; Daunorubicin; Anthracycline; zvířata; Rats; Disease Models, Animal; NADPH oxidase